Law and Christianity in Latin America : the work of great jurists - Mirow, Matthew C.; Domingo, Rafael (Law and religion, 2021)
"The book is a significant contribution to our ability to understand the work and perspectives of jurists and their effect on legal development in individual countries and the region. The individuals selected for study exhibit wide-ranging areas of expertise from private law and codification, through national public law and constitutional law, to international developments that left their mark on the region and the world. Each chapter discusses a jurist within his or her intellectual and political context. The jurists were selected after extensive consultation with legal historians in various countries of the region looking at jurist's particular merits, contributions to law in general, religious perspective, and importance within the specific country and period under consideration. All chapters have been written by distinguished legal scholars and historians from Latin America and around the world. This diversity of international and methodological perspectives gives the volume its unique character"--